Differentiation of volatile profiles of Thai Oolong tea No. 12 provenances by SPME-GC-MS combined with principal component analysis. (10th January 2018) - Pripdeevech, Patcharee; Rothwell, Joseph; D'Souza, Priya E.; Panuwet, Parinya
ABSTRACT: This work aimed to characterise and compare the volatile profiles of Oolong tea No. 12 obtained from eight provenances in Chiang Rai province of northern Thailand. Thirty-two samples were analysed using solid phase microextraction-gas chromatography-mass spectrometry (SPME-GC-MS). Sixty-seven volatile constituents were identified with their relative amounts. Principal Component Analysis (PCA) was used to compare profiles from all provenances and revealed three major clusters. The main volatile compounds responsible for the differentiation were linalool, geraniol, E-nerolidol, Z-jasmone, Z-methyl jasmonate, indole, and trans-linalool oxide. It appeared that the majority of the volatile compounds were significantly correlated with altitude. These resulting altitude-dependent profiles could be used as a means to improve or authenticate the products by local producers. This could be the first study to report the aromatic profiles from different Oolong teas planted and produced in northern Thailand.